Examination of Forensic Cases That are Consulted to the Başkent University Ankara Hospital Because of Traffic Accident - Yaşar, Zehtiye Füsun; Büken, Erhan (The Bulletin of Legal Medicine, 2015)
Objective: In this study the judicial notification reports of patients, who were consulted to the Emergency Department of of Başkent Unıversity Ankara Hospital as a result of traffic accident happened in the year 2013 was examined in retrospective way and besides the age, gender the place of the accident, type of accident, accident time, injury type and location, the aim was also the evaluation of the deficiencies of the prepared reports. Materials and Methods: The sample of the study, which has definitive feature is comprised of 2397 judicial notification reports, which were prepared in 2013 at Başkent University Ankara Hospital Emergency Service. The study includes the evaluation of 553 (23.07%) of traffic accidents of these reports. Results: The 553 judicial notification reports that were in the study include 38.52% women, 47.92% men, 6.51 % girl and 7.05% boy. 536 case, age information of which were reached, comprises of individuals which are between the ages of <18 (13.97%), 18-40 (51.95%), 41-63 (24,58%), ≥ 64 (9,49%). The 67.81% of the accidents are inside the vehicle, 29.48% of them are out of vehicle traffic accidents. Out of 407 cases with lesion findings, 329 have single system injuries. Head-neck (n:123, 30.23%) and lower extremity injuries (n: 101, 24.82%) rank first and second place respectively. The data of high consultation demand in orthopedic and neurosurgery clinics because of this localizations was obtained. It is determined that only 1.88% (n:10) of the injuries of the applied patients because of traffic accidents have vital risk...